A Corpus-based study of the synonyms cease, halt, and stop - Chaengchenkit, Rangsiya (LEARN Journal: Language Education and Acquisition Research Network, 2023)
This study aims to investigate the distribution across genres and the collocation of three synonymous verbs cease, halt, and stop. Data were from drawn from the Corpus of Contemporary American English (COCA). The results from the distribution across genres shed light on the degree of formality of each verb. The verb stop appears to have a low degree of formality since it occurs most frequently in the TV and movie subtitles genre, an informal genre and occurs least frequently in formal contexts, i.e., the genre of academic texts. The verbs cease and halt, in contrast, appear to have a higher degree formality as they occur least frequently in informal contexts, i.e., the spoken genre. Furthermore, it was found that the three verbs share certain collocates and themes, confirming their status as synonyms. However, despite these similarities, there are collocates and themes that are not shared. Hence, the synonymous verbs can be differentiated from each other based on the degree of formality and the collocation. Due to the difference in usage, they cannot be substitutable in all contexts.